Precision of Proximal Segment Repositioning Using Digitally Planned Custom Made guide in Sagittal Split Ramus Osteotomy - Adil Mustafa, Banu; N Aloosi , Suha (Diyala Journal of Medicine, 2023)
Background: Orthognathic surgery is widely used surgical procedure. The most common used orthognathic surgical procedure is bilateral sagittal split osteotomy (BSSO) that is used for managing skeletal mandibular excess, deficiency or asymmetry. Objective: To correct functional and aesthetic problems. Patients and Methods: A total of (12 patients) 24 condyles have been included in our study all with cl II malocclusion, open bites and asymmetry, both genders males and females, their age ranges between18 to 40 years, all the cases had preoperative and postoperative CT scans. Results: By comparing pre and post operative CT scans regarding condylar positions for both groups. The results revealed that there was less movement of condylar head in group with device and direction of movement was more favorable. Conclusion: This study showed that the Digitally Planned Custom Made guide was useful in repositioning condyles with minimal movement post operatively and more favorable direction of movement.